2007
DOI: 10.1007/s11886-007-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation or causation: Untangling the relationship between patent foramen ovale and migraine

Abstract: Observational evidence from the literature has shown an association between migraine headaches and patent foramen ovale (PFO). This observation has led to hypotheses that could explain the etiology of migraines in those with a PFO, including right-to-left shunting of venous agents such as serotonin that are normally broken down in the pulmonary circulation. Further evidence suggests that closure of a PFO may improve migraine symptoms and serve as an effective treatment modality for migraines. Several randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Right-to-left shunting through a PFO most commonly results from increased right atrial pressure, as occurs during the Valsalva maneuver or in the setting of severe pulmonary hypertension (Eisenmenger's syndrome), but anatomic factors such as prominent remnant eustachian valves can also contribute. 9 These factors were not apparent in this patient, but aortography demonstrated compression of the inferior vena cava by a secondary tumor, which could have had the effect of directing caval blood flow toward the PFO. Compression of this sort would increase the shunt, exposing the left side of the heart to toxic metabolites.…”
Section: Discussion Of Diagnosismentioning
confidence: 68%
“…Right-to-left shunting through a PFO most commonly results from increased right atrial pressure, as occurs during the Valsalva maneuver or in the setting of severe pulmonary hypertension (Eisenmenger's syndrome), but anatomic factors such as prominent remnant eustachian valves can also contribute. 9 These factors were not apparent in this patient, but aortography demonstrated compression of the inferior vena cava by a secondary tumor, which could have had the effect of directing caval blood flow toward the PFO. Compression of this sort would increase the shunt, exposing the left side of the heart to toxic metabolites.…”
Section: Discussion Of Diagnosismentioning
confidence: 68%
“…[ 6 ] Moreover, some vasoactive substances such as serotonin, which are normally degraded by the lung, bypass the lung to trigger brain arterioles and cause vasoconstriction, which induce hypoperfusion of the local brain tissue prone to cytotoxic edema. [ 7 ] Foong et al reported that the vasoconstriction of serotonin is more remarkable to arterioles than to main arteries such as the internal carotid and vertebral basilar artery. [ 8 ] The artery supplying the SCC are tiny and tortuous [ 9 ] ; hence, they are accessible to microemboli and sensitive to serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…The data for patients with CHD are similar to that reported in the PFO literature, where the incidence of MH also approaches 40% with a similar distribution pattern of aura to migraines without aura. 12,13 In assessing the role of intracardiac shunt in the pathogenesis of MH in adults with CHD, patients were divided into right-to-left, left-to-right, and no shunt groups. Although the prevalence was much higher than the control population for all 3 groups, there was no significant difference in the prevalence of MH among the groups with right-to-left (52%), left-to-right (44%), and no intracardiac shunt (40%) (p ϭ 0.12).…”
Section: Discussionmentioning
confidence: 99%